Penerapan Tema Desain Berkelanjutan Pada Gelanggang Remaja di Kabupaten Gianyar: Bahasa Indonesia - Made Gede Adi Upadana Arsitektur; I Putu Hartawan; I Nyoman Gede Maha Putra; Cokorda Istri Arina Cipta Utari (Undagi : Jurnal Ilmiah Jurusan Arsitektur Universitas Warmadewa, 2024)
Gelanggang Pemuda is a social platform for teenagers which is planned as a place for informal education for teenagers aged 10-22 years for self-development through activities they like, to expand their interests and talents. The planning and creation of this Youth Center is a solution to provide space for teenagers to fill their free time, which can be a place for youth communities and events that are focused and provide benefits. The basic consideration for planning this youth center is to look at existing youth phenom ena, for example juvenile delinquency which can be minimized with the proposed youth center. The function that will be focused on the youth arena also takes into account the interests of teenagers in Gianyar district, which include sports and the arts. This youth center will apply a sustainable design theme with the basic concept of creativity and recreation, this is related to the social behavior of teenagers who like to spend time in interesting places while honing their interests or talents to become more creative.